The Influence of Brand Ambassador, Brand Image, Product Quality, and Price on Purchasing Decisions at Rumah Kopi Renon - Kadek Githa Damayanti Wiputra; Gede Mekse Korri Arisena; A.A.A. Wulandira Sawitri Djelantik (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2022)
The coffee shop businesses in Bali especially in the Denpasar area are growing rapidly, making competition fierce between coffee shops in this area. Therefore, every company has to be able to maximize its competitive advantage and choose the right marketing strategy. One of the coffee shops in the Denpasar area is Rumah Kopi Renon which is a coffee shop from the coffee brand Bali Coffee Banyuatis which has been established since the 1960s so that it has a broad image. In building and maintaining a positive image, Bali Coffee Banyuatis has used the services of a brand ambassador as a marketing communication strategy. This study aims to: 1) Identify the characteristics of visitors, 2) Analyze the value of each variable 3) Analyze the influence of brand ambassadors, brand image, product quality, and price on purchasing decisions. The data analysis method in this study used Structural Equation Modeling-Partial Least Square (SEM-PLS) with a sample of 96 respondents. The results showed that the characteristics of the majority of visitors to Rumah Kopi Renon were aged 21-25 years old, the gender was male, were student, and had incomes ranging from less than 3 million rupiahs per month. It was found that the brand ambassador, brand image, product quality, and price had a positive and significant effect as evidenced by the acquisition of the value of each variable 2,115; 2,164; 2,699 and 2.115 on purchasing decisions at Rumah Kopi Renon.Keywords: coffee shop, brand ambassador, SEM-PLS